A Quasi-Experimental Examination of Telework Eligibility and Participation in the U.S. Federal Government. (December 2018) - Lee, David; Kim, Sun Young
This article examines the causal effects of telework eligibility and participation on employee attitudes, including perceived fairness, job satisfaction, and intention to stay, in the U.S. federal government. Drawing on the literatures on social exchange and organizational justice, we investigate how telework eligibility and participation influence employee attitudes and whether different reasons for nonparticipation have varying impacts. Our findings show that those employees who are eligible to telework report higher levels of perceived fairness, job satisfaction, and intention to stay than do those employees who are ineligible. On the other hand, the effects of telework participation on employee attitudes depend upon the reasons why nonparticipants do not telework. Specifically, when employees do not telework because of insufficient technical or managerial support, they report significantly lower levels of perceived fairness, job satisfaction, and intention to stay than do teleworkers. However, nontelework due to job requirements or personal choice does not have significant, negative effects on work attitudes.